The Height of Chitinous Ridges Alone Produces the Entire Structural Color Palette - Hemant Kumar Raut; Qifeng Ruan; Cédric Finet; Vinodkumar Saranathan; Joel K.W. Yang; Javier G. Fernandez (Advanced Materials Interfaces)
Abstract The colorful wings of butterflies result from the interaction between light and the intricate chitinous nanostructures on butterflies’ scales. This study demonstrates that just by reproducing the chitinous ridges present in butterfly scales (i.e., without any other secondary structure), the entire color palette is achieved. This result is achieved using a new methodology based on the controlled reproduction of parts of the biological structure of complex chitinous systems using their native chemistry, enabling the isolation of different features’ contributions. Here the contribution of the ridges and their variations as producing and modulating color hue is isolated. The results suggest that complicated butterfly scales may be non‐ideal solutions for producing color when multifunctionality is not considered.